The Implications of the Pacific Alliance on the Evolution of Inequality in Member Countries - Rojas-Lozano, Daniel (Latin American Journal of Trade Policy, 2018)
The Pacific Alliance is a regional integration process that seeks to promote greater economic growth, competitiveness and development in its member countries. In this paper, the author critically approaches this integration process and wonders if it affects the level of income inequality in their countries. When investigating the constituent agreements of the Pacific Alliance, and using Mercosur as a control group for the period 2000-2014, this study shows that the Pacific Alliance members conceive free capital flows as a mechanism to promote growth, however, the measures to promote this mechanism represent setbacks in distributive terms.